Are liquid levothyroxine formulations comparable? The LETI study - Elisa Gatta; Virginia Maltese; Ilenia Pirola; Elena Gandossi; Irene Silvestrini; Massimiliano Ugoccioni; Riccardo Morandi; Claudio Casella; Carlo Cappelli (Thyroid Research)
Abstract Background Liquid ethanol-containing levothyroxine (e-LT4) is known to circumvent malabsorption induced by food, drugs, or pathological conditions. Recently a new ethanol-free formulation of liquid levothyroxine (ef-LT4) has been commercialized. No studies have compared e-LT4 with ef-LT4. The aim of the present study is to compare thyroid hormone profile in patients treated with e-LT4 and ef-LT4. Material and methods We retrospectively retrieved thyroid hormonal profile and clinical data of 48 patients diagnosed with hypothyroidism who had been on stable treatment with an e- LT4 formulation at the same dosage for at least one year and who decided to switch to ef-LT4 for tasting issue. Results A significant increase in TSH levels was observed after 6 months on ef-LT4 treatment (2.5 ± 0.8 mIU/ml vs. 3.1 ± 1.0 mIU/ml, respectively, p < .001), while fT4 decreased [1.2 ng/dl (IQR 1.1–1.4) vs. 1.1 ng/dl (1.0–1.2), respectively, p = .047], maintaining the same dosage of LT4. In 31 patients, for whom data were available 12 months after the switch, TSH further increased (2.50 ± 0.9 mIU/ml at baseline vs 3.2 ± 0.9 mIU/ml after 6 months vs 3.5 ± 0.9 mIU/ml at 12 months, p < .001) and fT4 decreased [1.2 ng/dl (IQR 1.1–1.4) vs. 1.1 ng/dl (IQR 0.9–1.3) vs 1.0 ng/dl (IQR 0.9–1.1), p = .008]. Conclusion ef-LT4 formulation seems to be less effective compared to e-LT4 over time. However, further prospective cross-sectional studies, performed in large sets of patients, even on concomitant therapy with interfering drugs, are needed.